2021
DOI: 10.1016/j.cegh.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of deciding between home-discharge versus hospitalization in COVID-19 patients: The role of initial imaging and clinicolaboratory data

Abstract: Background/Objective It is important to predict the COVID-19 patient's prognosis, particularly in countries with lack or deficiency of medical resource for patient's triage management. Currently, WHO guideline suggests using chest imaging in addition to clinicolaboratory evaluation to decide on triage between home-discharge versus hospitalization. We designed our study to validate this recommendation to guide clinicians. This study providing some suggestions to guide clinicians for better decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In the absence of any COVID-19 vaccine in Iran (population, 79,926,270), the infection rate was 17.6 per 1000 (1,411,731 cases), and about 57,889 deaths were reported [3]. The average hospitalization and ICU admission rates were 42.2% and 15%, respectively [58].…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…In the absence of any COVID-19 vaccine in Iran (population, 79,926,270), the infection rate was 17.6 per 1000 (1,411,731 cases), and about 57,889 deaths were reported [3]. The average hospitalization and ICU admission rates were 42.2% and 15%, respectively [58].…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Although there were increasing positive evidences of CT to evaluate COVID-19 patients [ 3 , 7 , 22 , 23 ], it is not realistic way to perform CT scans for all huge COVID-19 patients in a pandemic. Radiation exposure of CT may be problematic even when using low dose in especially young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the quantitative assessment based on CT scan is required for the triaging of COVID-19 patients. A CT severity score was firstly reported by Pan et al [ 8 ] and it was subsequently used for disease classification and severity prediction [ 3 , 7 , 10 ]. Mozafari et al [ 3 ] suggested that CT scores <10 and ≧ 10 were indicators for home-discharge and hospitalization, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations